2020
DOI: 10.1002/mgg3.1462
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Forensic characteristics and phylogenetic analyses of one branch of Tai‐Kadai language‐speaking Hainan Hlai (Ha Hlai) via 23 autosomal STRs included in the Huaxia Platinum System

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 171 publications
(150 reference statements)
1
6
0
Order By: Relevance
“…S23, Supplementary Material online), in agreement with the time of linguistic divergence. Moreover, both previous studies ( He et al 2020 ; Li et al 2020 ) and our observations based on the f 3 tests indicated that HNL was an isolated population with low gene flow compared with other mainland Bai-Yue populations. The f 4 tests of our study also illustrated that, compared with the mainland Bai-Yue populations, HNL show closer genetic connections with ancient southern East Asian ancestry and Austronesian-related ancestry, which may also be preserved by the early migration to Hainan Island.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…S23, Supplementary Material online), in agreement with the time of linguistic divergence. Moreover, both previous studies ( He et al 2020 ; Li et al 2020 ) and our observations based on the f 3 tests indicated that HNL was an isolated population with low gene flow compared with other mainland Bai-Yue populations. The f 4 tests of our study also illustrated that, compared with the mainland Bai-Yue populations, HNL show closer genetic connections with ancient southern East Asian ancestry and Austronesian-related ancestry, which may also be preserved by the early migration to Hainan Island.…”
Section: Discussionsupporting
confidence: 76%
“…These studies suggest that HNL manifested a close genetic relationship with indigenous populations in South China, where the Bai-Yue ancestors were believed to be widely distributed, while also retaining a unique genetic background. However, previous studies of the HNL have focused on forensic characteristics or uniparental genetic markers ( Li, Li, Ou, et al 2008 ; Peng et al 2011 ; Li et al 2013 ; Fan et al 2018 ; Song et al 2019 ; Li et al 2020 ; Mengge et al 2020 ) and have therefore failed to portray the full picture of genetic history and adaptive evolution of HNL. In addition, due to the limited amount of genetic material, small sample size, and analytical approaches, conclusions drawn from previous studies are contradictory and may show bias concerning the fine-scale population history of HNL.…”
Section: Introductionmentioning
confidence: 99%
“…The 44 A-InDels of UAIS possessed relatively reasonable genetic information (PIC > 0.25) ( Botstein et al, 1980 ), and the UAIS with the CMP range of 1.27 × 10 –18 to 1.03 × 10 –14 for 27 universal human populations satisfied the requirements for forensic human identification (10 –15 –10 –14 ) ( Pereira et al, 2009 ), which indicated that the UAIS could be considered as a powerful tool for human identification. Compared with the CPE provided by the common STR panels ( Fan et al, 2019a ; Fan et al, 2019b ; Li et al, 2020 ), CPE for UAIS has outclassed 0.993634–0.999908. Therefore, the UAIS could supply additional information for the paternity tests.…”
Section: Resultsmentioning
confidence: 90%
“…To obtain a broader picture of population relationships within Southeast Asia, we included publicly available STR frequency from relevant populations [ 15 , 21 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] and a neighbor-joining tree (NJ) based on F st computation by allele frequency from 13 STRs of the FBI Laboratory’s Combined DNA Index System (CODIS) was carried out using POPTREE v.2 [ 58 ].…”
Section: Methodsmentioning
confidence: 99%